2023
DOI: 10.1002/ejhf.2767
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying inflammation using interleukin‐6 for improved phenotyping and risk stratification in acute heart failure

Abstract: Systemic inflammation may be central in the pathophysiology of acute heart failure (AHF). We aimed to assess the possible role of systemic inflammation in the pathophysiology, phenotyping, and risk stratification of patients with AHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…We wish to thank Wang and colleagues for their interest in our work investigating the role of systemic inflammation, as quantified by interleukin-6, in the pathophysiology, phenotyping, and risk stratification of patients with acute heart failure (AHF). 1 We fully agree with Wang and colleagues that the association of interleukin-6 with cardiovascular death as additional endpoint should also be explored. All-cause mortality, which was the primary endpoint in our study, is the most commonly used and most important endpoint in heart failure (HF) trials.…”
supporting
confidence: 69%
“…We wish to thank Wang and colleagues for their interest in our work investigating the role of systemic inflammation, as quantified by interleukin-6, in the pathophysiology, phenotyping, and risk stratification of patients with acute heart failure (AHF). 1 We fully agree with Wang and colleagues that the association of interleukin-6 with cardiovascular death as additional endpoint should also be explored. All-cause mortality, which was the primary endpoint in our study, is the most commonly used and most important endpoint in heart failure (HF) trials.…”
supporting
confidence: 69%
“…Leptin, fatty acid-binding protein 4, interleukin-1 receptor antagonist, tumour necrosis factor receptor superfamily member 11 and proto-oncogene tyrosine-protein kinase receptor Ret were the most elevated in patients with metabolic syndrome, showing the involvement of inflammatory activation. 12 Michou et al 13 quantified systemic inflammation using a novel interleukin-6 immunoassay in 2042 unselected patients presenting at the emergency department with acute dyspnoea. Half of these patients had a diagnosis of acute HF and presented higher levels of interleukin-6 compared to patients with other causes of dyspnoea.…”
Section: Inflammationmentioning
confidence: 99%
“…In brief, the study, which comprised 2042 patients presenting with acute dyspnoea, including 1026 patients with AHF, demonstrated that a very high proportion (83.7%) of patients with AHF had elevated IL-6 levels and IL-6 was an independent predictor of 1-year all-cause mortality. 1 We appreciate the valuable findings of Michou et al 1 Systemic inflammation is recognized to play a vital role in heart failure. 2 The study by Michou et al 1 adds strong and direct evidence for the association between inflammation and prognosis in patients with AHF.…”
mentioning
confidence: 95%
“…1 We appreciate the valuable findings of Michou et al 1 Systemic inflammation is recognized to play a vital role in heart failure. 2 The study by Michou et al 1 adds strong and direct evidence for the association between inflammation and prognosis in patients with AHF. However, we thought to discuss two important issues.…”
mentioning
confidence: 95%
See 1 more Smart Citation